CCS - Failing to Pass Decision Gates - Magne Emhjellen; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
There is a planning gap for CCS projects in Europe. CCS demonstration plants are not implemented as expected. This fact is at odds with optimistic valuation reports that apply socio-economic valuation criteria for climate projects. However, CCS plants are in most cases to be implemented by private companies. Economic valuation of climate projects, seen from the perspective of the commercial companies, is the subject of this article. We examine key economic parameters of 27 oil and gas projects and compare it to a CCS project. We find that the CCS project ranks the lowest on all profitability metrics, and is unlikely to be implemented by a private company. Our findings may explain why it is hard for oil companies to justify climate projects in their portfolios.
Keywords: M21; G38; G31; Q51; Q48; 330; climate projects; decision analysis; CO2